2019
DOI: 10.1039/c8ee02184h
|View full text |Cite|
|
Sign up to set email alerts
|

A review of crystalline silicon bifacial photovoltaic performance characterisation and simulation

Abstract: This paper presents a review on crystalline silicon bifacial PV performance characterisation and simulation to facilitate new research developments for bifacial PV technology and implementation in the global market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(103 citation statements)
references
References 79 publications
0
102
0
1
Order By: Relevance
“…Collecting photons on both sides of Si photoelectrode is a promising option to further improve the light utilization efficiency per unit area. [ 29 ] The photocurrent and H 2 production velocity will be further increased if the photoelectrode could collect photons from the front and back sides simultaneously. However, the Si photoelectrode with bifacial photon‐collecting ability for water splitting has rarely to be reported due to the short carrier diffusion length.…”
Section: Resultsmentioning
confidence: 99%
“…Collecting photons on both sides of Si photoelectrode is a promising option to further improve the light utilization efficiency per unit area. [ 29 ] The photocurrent and H 2 production velocity will be further increased if the photoelectrode could collect photons from the front and back sides simultaneously. However, the Si photoelectrode with bifacial photon‐collecting ability for water splitting has rarely to be reported due to the short carrier diffusion length.…”
Section: Resultsmentioning
confidence: 99%
“…Researches demonstrated for bifacial and indoor PV that the impact of surroundings is even more pronounced on solar spectral distribution then daily, seasonal and/or weather impact. 55 Recently, it has been shown that the efficiency of bifacial PV cells 56 is bound to spectral albedo 57 and albedo itself is not only spectrally dependent but also dependent on the morphology of surrounding environment. 55 This means, even the geometry of the measurement equipment and, for indoor application, of the room might affect the bifacial cell efficiency.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…The potential of bifacial photovoltaic (PV) systems over their monofacial counterpart—either fixed tilt or tracking—in terms of energy yield has been widely proved by pilot installations as well by simulations . However, the accuracy of energy yield prediction of bifacial PV systems is largely debated, which makes the bankability of bifacial technology uncertain to some extent; as a result, more experiments dealing with bifacial PV systems at various installation conditions and locations are needed to further evaluate the existing simulation models.…”
Section: Introductionmentioning
confidence: 99%